Added value of multimodal computed tomography imaging: analysis of 1994 acute ischaemic strokes. (1st November 2016) - Bill, O.; Faouzi, M.; Meuli, R.; Maeder, P.; Wintermark, M.; Michel, P.
Abstract : Background and purpose: Multimodal computed tomography (CT) based imaging (MCTI) is widely used in acute ischaemic stroke. It was postulated that the use of MCTI is associated with improved patient outcome without causing harm. Methods: All patients with an acute ischaemic stroke and CT‐based imaging within 24 h from the ASTRAL (Acute Stroke Registry and Analysis of Lausanne) registry were included. Preceding demographic, clinical, biological, radiological and follow‐up data were collected. Significant predictors of MCTI use were identified retrospectively to go on to fit a multivariable analysis. Then, patients undergoing additional CT angiography (CTA) or CTA and perfusion CT (CTP) were compared with non‐contrast CT only patients with regard to 3‐month favourable outcome (modified Rankin Scale score ≤2), 12‐month mortality, stroke mechanism, short‐term renal failure, use of ancillary diagnostic tests, duration of hospitalization and 12‐month stroke recurrence. Results: Of the 1994 included patients, 273 had only non‐contrast CT, 411 had both non‐contrast CT and CTA and 1310 had all three examinations. Factors independently associated with MCTI were younger age, low pre‐stroke modified Rankin Scale score, low creatinine value, known stroke onset, anterior circulation stroke, anticoagulation or antihypertensive therapy (CTA only) and higher National Institutes of Health Stroke Scale scores (CTP only). After adjustment, MCTI was associated with a 50% reduction of 12‐month mortality and a lower likelihood of unknown stroke mechanism. No association was found between MCTI and 3‐month outcome, contrast‐induced nephropathy, hospitalization duration, number of ancillary diagnostic tests or with stroke recurrence. Conclusion: Our study shows an association of MCTI use with lower adjusted 12‐month mortality, better identification of the stroke mechanism and no signs of harm.